An Update on Treatment and Management of Pediatric Systemic Lupus Erythematosus. Issue 2 (December 2016) - Thakral, Amit; Klein-Gitelman, Marisa
Abstract Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disorder in which 20 % of patients are diagnosed in childhood. Childhood-onset SLE is associated with higher morbidity and mortality than adult-onset SLE. The aims of disease management with early immunosuppression are to decrease disease activity and improve quality of life. A multidisciplinary approach is necessary due to the complexity of lupus in pediatric patients. It is important to provide patients with high quality of care and to instill ownership of their disease process from a young age to prepare them to manage this life-long illness. This article reviews current management of SLE in children.